2015
DOI: 10.1155/2015/942059
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Design Patterns for Modern Fortran

Abstract: This paper presents ideas for using coordinate-free numerics in modern Fortran to achieve code flexibility in the partial differential equation (PDE) domain. We also show how Fortran, over the last few decades, has changed to become a language well-suited for state-of-the-art software development. Fortran’s new coarray distributed data structure, the language’s class mechanism, and its side-effect-free, pure procedure capability provide the scaffolding on which we implement HPC software. These features empower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Paper [37] investigates how a DSL can provide better maintainability while keeping good efficiency. Paper [38] describes design patterns for FORTRAN for modern, maintainable software which is still efficient. Paper [39] reports on the experience of using existing frameworks especially for infrastructure and data management to improve extensibility while keeping high efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paper [37] investigates how a DSL can provide better maintainability while keeping good efficiency. Paper [38] describes design patterns for FORTRAN for modern, maintainable software which is still efficient. Paper [39] reports on the experience of using existing frameworks especially for infrastructure and data management to improve extensibility while keeping high efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Only one paper was published as a technical report and, hence, definitely non-refereed. [33], [34], [35], [36], [37], [27], [40], [30], [41], [31], [43], [32], [44] Empirical study without intervention 11 [18], [22], [24], [26], [15], [29], [19], [42], [20], [17], [21] Empirical study with intervention 5 [23], [38], [39], [25], [28] Opinion/philosophical paper 4 [13], [14], [2], [16] We also classified the included article in different types. We show the results in Tab.…”
Section: Scalability Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Haveraaen et al [23] observed that, even for large messages, the Intel compiler was performing element-wise transfer when Coarray Fortran was used for communication. similar (till 96 cores) or in some cases (192 and 384 cores) better than the MPI version.…”
Section: Performancementioning
confidence: 99%
“…CAF's speedup performance was found to be 3.6% higher on average than the ideal value. This superlinear speedup is caused by cache effects [20]. More data can be stored in caches as the number of processors increases.…”
Section: Parallel Solution Times and Speedupsmentioning
confidence: 99%